Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
DOI: 10.1007/978-3-540-69369-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Writing with Your Eye: A Dwell Time Free Writing System Adapted to the Nature of Human Eye Gaze

Abstract: Abstract. We investigate the usability of an eye controlled writing interface that matches the nature of human eye gaze, which always moves and is not immediately able to trigger the selection of a button. Such an interface allows the eye continuously to move and it is not necessary to dwell upon a specific position to trigger a command. We classify writing into three categories (typing, gesturing, and continuous writing) and explain why continuous writing comes closest to the nature of human eye gaze. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Some of the possible approaches include the use of eye gestures for writing individual letters [Isokoski 2000;Sarcar et al 2013;Chakraborty et al 2014;Bee and André 2008;Wobbrock et al 2008], eye typing via context switching [Morimoto and Amir 2010], and visual navigation of nested boxes of letters [Ward et al 2000;Rough et al 2014]. Although these works demonstrate the possibility of dwell-free eye typing, the user must learn a new way to write a letter rather than simply looking at where the intended keys would be found on a QWERTY keyboard layout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the possible approaches include the use of eye gestures for writing individual letters [Isokoski 2000;Sarcar et al 2013;Chakraborty et al 2014;Bee and André 2008;Wobbrock et al 2008], eye typing via context switching [Morimoto and Amir 2010], and visual navigation of nested boxes of letters [Ward et al 2000;Rough et al 2014]. Although these works demonstrate the possibility of dwell-free eye typing, the user must learn a new way to write a letter rather than simply looking at where the intended keys would be found on a QWERTY keyboard layout.…”
Section: Introductionmentioning
confidence: 99%
“…The discussed adaptations of different schemes-Morse code, MDITIM, Quikwriting, and Cirrin-for decoding target hit sequences into text, but did not validate the technique with controlled experiments. Quikwriting, which was originally created for pen-based computers, was also evaluated as a potential eye typing method in the work by Bee and André [2008]. In a controlled experiment with three participants, Quikwriting supported a typing rate of 5.0WPM, which was slower than the 7.8WPM rate achieved with their implementation of a dwell-based keyboard that used a dwell duration of 750ms.…”
Section: Introductionmentioning
confidence: 99%
“…Huckauf and Urbina [19], Bee and André [4], Wobbrock et al [64] suggested the use of gaze gestures to enter individual characters. A specific sequence of eye movements is required for each character.…”
Section: A Publications 87mentioning
confidence: 99%
“…Bee and André [4] adapted the stylus-based interface of Quikwriting, introduced by Perlin [44], for gaze input. The central area of the interface, called resting area shows groups of up to five characters.…”
Section: Quikwritingmentioning
confidence: 99%
“…Some of the possible approaches include the use of eye-gestures for writing individual letters [Bee and André, 2008;Chakraborty et al, 2014;Isokoski and Raisamo, 2000;Sarcar et al, 2013;Wobbrock et al, 2008], context switching eye-typing [Morimoto and Amir, 2010], and visually navigating nested boxes of letters [Rough et al, 2014;Ward et al, 2000]. Although these works demonstrate the possibility of dwell-free eye-typing, the user must learn a new way to write a letter rather than simply looking at where the intended keys would be found on a QWERTY keyboard layout.…”
Section: Introductionmentioning
confidence: 99%